Quality‐based procedures in Ontario: exploring health‐care leaders' responses. (25th November 2014) - Baxter, Pamela; Cleghorn, Laura; Alvarado, Kim; Cummings, Greta; Kennedy, Deborah; McKey, Colleen; Pfaff, Kathy
Abstract : Aim: To examine health‐care leaders' initial response to the implementation of orthopaedic quality based procedures (QBPs) in hospitals across Ontario, Canada. Background: In 2012, Ontario, Canada shifted 91 hospitals to a patient‐based funding (PBF) approach. This approach funds health‐care organisations based on the number of patients treated with select procedures known as QBPs. Methods: An exploratory descriptive design was employed to better understand health‐care leaders' early implementation experiences. Seventy organisational leaders from 20 hospitals participated in six focus groups and four interviews to discuss their initial responses to the implementation of two QBPs (primary unilateral hip replacement and primary unilateral knee replacement). Qualitative data underwent content analysis. Findings: Three key major themes emerged; (1) responding to change, (2) leading the change and (3) managing the change. Within each of these themes, barriers and benefits were identified. Conclusion: Leaders are accepting of PBF and QBPs. However, challenges exist that require further exploration including the need for a strong infrastructure, accurate and timely clinical and financial data, and policies to prevent unintended consequences. Implications for nursing management: Implementing QBPs requires careful planning, adequate and appropriate resources, vertical and horizontal communication strategies, and policies to ensure that unintended consequences are avoided and positive outcomes achieved.